The Arch, Adams Square, 1930 - Unknown (Tufts Archival Research Center, 2005)
Elevated view looking southwest from Faneuil Hall toward Dock and Adams Squares. Spectators are watching a procession of Legionnaires in the National American Legion parade turning onto Congress Street from Adams Square. In the lower left corner of the image is the statue of John Adams which is located in front of Faneuil Hall. 7 1/2 x 9 7/16 overall 8 x 10 Photographs